Project-Based Learning for Assemblr Edu Augmented Reality Media: Products and Experiences of Primary School Teacher Education Students - Fauziah, Nurul; Khusaini, Fakhri; Ummah, Rakhmatul (LITPAM, 2026)
The development of digital technology requires prospective teachers to have the ability to design innovative, technology-based learning media. This study, involving 35 primary school teacher education students, aims to describe the implementation of Project-Based Learning (PjBL) in the development of Augmented Reality (AR)-based learning media using Assemblr Edu and to examine the products and learning experiences of the students. This study uses a qualitative descriptive approach with a case study design. The research subjects consisted of 35 primary school teacher education students taking the Learning Multimedia course. Data were collected through observation, interviews, and documentation of students' AR products. Data analysis was carried out using the Miles, Huberman, and Saldaña model through the stages of data condensation, data display, and conclusion drawing. The results showed that the implementation of PjBL was carried out in a